T Cell Distribution in Relation to HIV/HBV/HCV Coinfections and Intravenous Drug Use - Kallas, Eveli (Viral Immunol, 2016)
Intravenous drug use (IDU) is one of the most important transmission routes for blood borne viruses, including human immunodeficiency virus (HIV), hepatitis B virus (HBV), and hepatitis C virus (HCV). These infections alter the subset distributions of T cells; however, knowledge of such effects during HIV, HBV, and or HCV coinfection is limited. Therefore, we aimed to evaluate any associations between T cell distribution and the presence of HIV, HBV, and HCV coinfections among persons who inject drugs (PWID). Blood samples from 88 Caucasian PWID (mean age 30; 82% male) and 47 age-matched subjects negative for all three infections (mean age of 29; 83% male) were analyzed. The T cell markers CD3, CD4, CD8, CD45RA, CCR7, HLA-DR, and CCR5 were assessed using flow cytometry. Of the PWID, 40% were HIV+HBV+HCV+, 20% HBV+HCV+, 19% HCV+, and 13% negative for all three infections. The HIV+HBV+HCV+ PWID had lower percentages of CD4(+) and higher percentages of CD8(+) cells compared to triple negative PWID (p < 0.001 in all cases). The only difference between HBV+HCV+ with triple negative PWID was the lower CD4(+) cell percentages among the former (52.1% and 58.6%, p = 0.021). Triple negative PWID had higher immune activation and number of CCR5(+) cells compared to the controls. We suggest that the altered T cell subset distribution among PWID is mainly triggered by HIV infection and or IDU, while HBV and or HCV seropositivity has minimal additional effects on CD4(+) cell distribution.